A method for real-time estimation of full-scale global ice loads on floating structures - Kjerstad, Øivind Kåre; Lu, Wenjun; Skjetne, Roger; Løset, Sveinung (Cold Regions Science and Technology, 2018)
This paper proposes an algorithm that uses conventional measurements found on-board ships coupled with additional Inertial Measurement Units to estimate the motions and global loads acting on them. The work is motivated by the scarce availability of full-scale load data for sea-ice operations and by the invasive instrumentation of strain gauges used to obtain global loads of all degrees of freedom. Full-scale data are key to a number of design, operational, and research aspects related to sea-ice operations. The proposed algorithm is based on four Inertial Measurement Units (IMUs) that together with position and heading measurements are used to make estimates of dynamic linear and rotational acceleration (acceleration resulting in motion). We show how to use models updated with propulsion and wind measurements to estimate propulsion, hydrodynamic, wind, and ice loads through a setup catering to real-time implementation. A case study with the Swedish icebreaker Oden is presented and discussed. The algorithm effectively yields reasonable ice load history estimations and presents great potential in its further application to real-time global ice load estimations. acceptedVersion © 2018. This is the authors’ accepted and refereed manuscript to the article. Locked until 13.3.2020 due to copyright restrictions. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/